2021
DOI: 10.2196/28128
|View full text |Cite
|
Sign up to set email alerts
|

A Wearable Activity Tracker Intervention With and Without Weekly Behavioral Support Emails to Promote Physical Activity Among Women Who Are Overweight or Obese: Randomized Controlled Trial

Abstract: Background Physical activity (PA) plays a fundamental role in combating the current obesity epidemic; however, most women who are overweight or obese are generally physically inactive. Wearable activity tracker interventions can help increase the PA levels in this population. Supplementing such interventions with behavioral support emails may further improve their effectiveness, but this remains to be confirmed. Objective This study aims to determine if… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 51 publications
2
13
0
Order By: Relevance
“…This study explored the acceptability of a theory-driven, email-delivered intervention within the context of a larger, single centre, unblinded, three-arm parallel group RCT; the effects of the intervention were compared to a very low-contact intervention (i.e., wearable activity tracker only) and a control condition to promote PA in women who were overweight or obese and insufficiently active (see Table 1 for an overview of the three arms, and (7) for further description). Specifically, the objectives of the larger trial were to: (a) assess changes in PA within each group and determine if there were significant differences in changes in PA between groups, and (b) explore changes in PA-related basic psychological needs satisfaction and motivational regulations within and between groups to gain more insight into any observed changes (or lack thereof) in PA. As reported by Black and Brunet (7), women randomized to the main intervention reported a significant increase in walking and in perceptions of competence and relatedness, though not in moderate-to-vigorous intensity PA, nor in perceptions of autonomy and motivation. Participants' responses could have been influenced by their subjective perceptions of the intervention, as well as their measurable sustained engagement with the intervention.…”
Section: Methodssupporting
confidence: 63%
See 3 more Smart Citations
“…This study explored the acceptability of a theory-driven, email-delivered intervention within the context of a larger, single centre, unblinded, three-arm parallel group RCT; the effects of the intervention were compared to a very low-contact intervention (i.e., wearable activity tracker only) and a control condition to promote PA in women who were overweight or obese and insufficiently active (see Table 1 for an overview of the three arms, and (7) for further description). Specifically, the objectives of the larger trial were to: (a) assess changes in PA within each group and determine if there were significant differences in changes in PA between groups, and (b) explore changes in PA-related basic psychological needs satisfaction and motivational regulations within and between groups to gain more insight into any observed changes (or lack thereof) in PA. As reported by Black and Brunet (7), women randomized to the main intervention reported a significant increase in walking and in perceptions of competence and relatedness, though not in moderate-to-vigorous intensity PA, nor in perceptions of autonomy and motivation. Participants' responses could have been influenced by their subjective perceptions of the intervention, as well as their measurable sustained engagement with the intervention.…”
Section: Methodssupporting
confidence: 63%
“…A complete description the primary (i.e., PA behaviour) and secondary outcome measures (i.e., PA-related basic psychological needs satisfaction and motivational regulations), including how and when they were used, is available in Black and Brunet (45). Results of analyses performed for primary and secondary outcomes are reported elsewhere (7). Pertinent to the current study, participants self-reported sociodemographic and health information (e.g., age, marital status, ethnicity, education, work status, smoking status) at baseline within an online survey using the platform SurveyMonkey.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The utility of behavioral economics is vast, and digital health has leveraged the discipline, allowing researchers to investigate how people use digital health programs and obtain insights on the characteristics of people who use them. Several digital health studies have investigated the use of several strategies, including the use of cooperative games and incentives [ 25 ], gamification [ 26 , 27 ], serious games [ 28 , 29 ], and positive behavioral support [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%